ByzRev 06.2024.037: Alexander Alexakis – Dimitrios S. Georgakopoulos (Hrsg.), Kalligraphos – Essays on Byzantine Language and Literature and Palaeography, from Byzantine Historiography to Post-Byzantine Poetry.: Festschrift in Honour of Ioannes Mavromatis (Byzantinisches Archiv 42). Berlin – Boston: Walter de Gruyter, 2023. - Hinterberger, Martin (The Byzantine Review, 2024)
Alexander Alexakis – Dimitrios S. Georgakopoulos (Hrsg.), Kalligraphos – Essays on Byzantine Language and Literature and Palaeography, from Byzantine Historiography to Post-Byzantine Poetry. Festschrift in Honour of Ioannes Mavromatis (Byzantinisches Archiv 42). Berlin – Boston: Walter de Gruyter, 2023. XIV, 383 S. – ISBN 978-3-11-100981-0